Association of working conditions including digital technology use and systemic inflammation among employees: study protocol for a systematic review - Helena C. Kaltenegger; Linda Becker; Nicolas Rohleder; Dennis Nowak; Matthias Weigl (Systematic Reviews, 2020)
Abstract Background With the dynamic advancement of digitalization, working environments are changing and risk for employee stress may be increasing. Work stress has been associated with a dysregulation of inflammatory processes as a component of immune function. Systemic low-grade inflammation is discussed as a key player in the relation between stress exposure and chronic illness, such as cardiovascular diseases. The objective of this investigation will be to evaluate the association of working conditions including digital technology use and systemic inflammation among employees. Methods We designed and registered a study protocol for a systematic review of randomized controlled trials and prospective non-randomized studies (e.g., cohort, interrupted time series, or before-after studies). We will include studies conducted among adult workers reporting associations of working conditions and inflammatory activity. The outcome will be biomarkers of systemic low-grade inflammation on cell, plasma molecule and intracellular level, such as C-reactive protein, or different types of leukocytes, cytokines, etc. Literature searches will be conducted in several electronic databases (from January 1982 onwards), including PubMed/MEDLINE, Embase, PsycINFO, Web of Science, and CENTRAL. Two reviewers will independently screen all retrieved records, full-text articles, and extract data. The study methodological quality (or bias) will be appraised using appropriate tools. Our results will be described qualitatively. Random effects meta-analysis will be conducted, if feasible and appropriate. Additional analyses will be performed to explore potential sources of heterogeneity. Discussion This systematic review and meta-analysis will provide a synthesis of studies evaluating the association of working conditions and systemic inflammation. We anticipate our findings to identify knowledge gaps in the literature that future research should address. Moreover, results of our review may provide implications for corporate and public policy action for employee health promotion and prevention of occupational stress. Systematic review registration PROSPERO ID: CRD42020166887